Functional analysis of mutations endowing rAAV2-retro with retrograde tracing capacity. (27th July 2022) - Zhang, Yujing; Wang, Jingyi; Li, Jiamin; Chen, Yefei; Sun, Jing; Lu, Zhonghua; Li, Yuantao; Liu, Taian
Highlights: The role of mutations enabling AAV2 to undergo retrograde transport is individually analyzed. Decapeptide insertion is pivotal for the retrograde functionality. V708I could be dispensable and even deleterious depending on the projection neurons. Abstract: Recombinant adeno-associated viruses (rAAVs) are widespread vectors in neuroscience research. However, the nearly absent retrograde access to projection neurons hampers their application in functional dissection of neural circuits and in therapeutic intervention. Recently, engineering of the AAV2 capsid has generated an AAV variant, called rAAV2-retro, with exceptional retrograde functionality. This variant comprises a 10-mer peptide insertion at residue 587 and two point mutations (LADQDYTKTA + V708I + N382D). Here, we evaluated the contribution of each mutation to retrograde transport in prefrontal cortex -striatum and amygdala-striatum pathways, respectively. Results showed that disruption of the inserted decapeptide almost completely abolishes the retrograde access to neurons projecting to striatum. Eliminating N382D has little effect on the retrograde functionality. Restoring another mutation V708I, however, even improves its performance in amygdala-striatum pathway. Parallel comparison within same animal further confirms this conflicting effect of V708I. These results demonstrate a pivotal role of decapeptide insertion in gaining the capacity of retrograde transport and highlight a neural circuit-dependent contribution of V708I. It suggests constant and custom engineering of rAAV2-retro might be required to tackle the challenge of tremendous neuronal heterogeneity.